Improving Quality of Life for Bedridden Patients : Introducing [Chilly] - Sham Shurpali (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Bedridden patients face a unique set of challenges that can significantly impact their quality of life. This paper introduces [Chilly], a novel product designed to address specific needs of bedridden individuals, enhancing their comfort, independence, and overall well-being.